Cobalt bis(dicarbollide) is a DNA-neutral pharmacophore - Fink, Krzysztof; Cebula, Jakub; Tošner, Zdeněk; Psurski, Mateusz; Uchman, Mariusz; Goszczyński, Tomasz M (Dalton transactions (Cambridge, England, 2023)
Cobalt bis(dicarbollide) (COSAN) is a metallacarborane used as a versatile pharmacophore to prepare biologically active hybrid organic-inorganic compounds or to improve the pharmacological properties of nucleosides, antisense oligonucleotides, and DNA intercalators. Despite these applications, COSAN interactions with nucleic acids remain unclear, limiting further advances in metallacarborane-based drug development. Although some studies showed that COSAN intercalates into DNA, COSAN-containing intercalators do not, and while COSAN shows low cytotoxicity, intercalators are often highly toxic. The present study aimed at comprehensively characterizing interactions between COSAN and DNA using a wide range of techniques, including UV-Vis absorption, circular (CD) and linear (LD) dichroism, nuclear magnetic resonance (NMR) spectroscopy, thermal denaturation, viscosity, differential scanning calorimetry (DSC), isothermal titration calorimetry (ITC), and equilibrium dialysis measurements. Our results showed that COSAN has no effect on DNA structure, length, stability, or hybridization, with no or only faint signs of COSAN binding to DNA. Moreover, DNA is not necessary for COSAN to induce cytotoxicity at high concentrations, as shown by in vitro experiments. These findings demonstrate that COSAN is a DNA-neutral pharmacophore, thus confirming the general safety and biocompatibility of metallacarboranes and opening up new opportunities for further developing metallacarborane-based drugs.
Keywords: interkalátory; Pharmacophore; DNA; farmakofor; Intercalating Agents; Circular Dichroism; kobalt; Cobalt; cirkulární dichroismus